Non-Q wave myocardial infarction : Groote Schuur Hospital Coronary Care Unit 1990-1993 - Okreglicki, Andrzej Michael (Division of Cardiology, 2018)
Non-Q Myocardial Infarction (NQMI) is considered to be an unstable condition with increased risk of recurrent infarction. Thus aggressive approaches in management have been recommended. However, there is no firm evidence that this strategy influences the course of NQMI patients favourably. To determine the experience at Groote Schuur Hospital all patients admitted to CCU from 1990 to 1993 with NQMI were analysed retrospectively especially with regard to management and outcome. One-hundred and eighty-one patients were admitted with NQMI. Seventy-eight percent (141) remained cardiovascularly stable in the early period after the index event; 51% (93) underwent cardiac catheterisation during that hospital admission and revascularization was performed in 29% (52). There were 2 deaths during the initial hospital admission, both after surgical revascularisation. At one year the cardiac mortality was 7%. There were 23 cardiac deaths in all. Early readmission for symptomatic recurrence of ischaemia was identified as a risk factor (p=0.004). By one year 51% of patients had developed recurrence of symptomatic ischaemia, the majority (62%) in the first 3 months after the primary admission. There was a significantly reduced recurrence in those patients managed actively (i.e. cardiac catheterisation with/without revascularization) as compared to those treated conservatively (p=0.001).